Managing IT outsourcing performance - Solli-Saether, Hans.; Gottschalk, Petter, 1950- (Hershey, PA : Business Science Reference, 2010)
'This book provides a collection of methodologies and tools that can be used in managing relationships and performance of IT outsourcing'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Information technology -- Management; Contracting out; Electronic data processing departments -- Contracting out